THE POSSIBILITY OF COPROCESSING MUNICIPAL SOLID WASTE - MSW IN CLINKER KILNS TO CEMENT PRODUCTION - Meystre, J. A.; Silva, R. J. (Revista de Engenharia Térmica, 2013)
The objective of this paper is to present an analysis of coprocessing in a cement production plant using Municipal Solid Waste - MSW as a secondary fuel and show the main advantages that burn into a incineration plant. The manufacture of Portland cement is a process that requires a large consumption of thermal and electrical energy and front of the immense worldwide energetic demand has increased its value every day. The typical operating cost involving this energy achieves 40% of the final product and due to increasing world consumption justifies the efforts to reduce the costs associated with its production. The use of high efficiency equipment coupled with the replacement of fossil fuels and conventional raw material for alternative products has given good results. The method of disposal of MSW in landfills in large urban centers is being used less and less. The creation of environmental laws increasingly severe shortages of allied areas not disturbed and the high cost of construction and operation of landfills hinders its viability. Moreover, there is a problem related to the emissions of gaseous and liquid effluents that help raise the cost for its control and treatment. The MSW, when recovered and separated, can become recyclable products and as energy sources. After separation of the usable material (organic matter and recyclable), remaining MSW materials with sufficient calorific value can be used in kilns to produce clinker. Moreover, the ash resulting from combustion may be incorporated in the clinker decreasing the initial amount of raw material. The use of MSW as alternative fuel has shown to be feasible in the clinker kiln, but their use is still limited by their availability, since their segregation is rarely practiced. The substitution of alternative inputs introduce restrictions to the process which must be safely handled in order to ensure the minimum quality and productivity of cement production plants. The use of MSW must have a thorough characterization of your composition, because of directly influences in the final product.